2013
DOI: 10.1371/journal.ppat.1003120
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Siderophore Export System Essential for Virulence of Mycobacterium tuberculosis

Abstract: Iron is an essential nutrient for most bacterial pathogens, but is restricted by the host immune system. Mycobacterium tuberculosis (Mtb) utilizes two classes of small molecules, mycobactins and carboxymycobactins, to capture iron from the human host. Here, we show that an Mtb mutant lacking the mmpS4 and mmpS5 genes did not grow under low iron conditions. A cytoplasmic iron reporter indicated that the double mutant experienced iron starvation even under high-iron conditions. Loss of mmpS4 and mmpS5 did not ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
247
2
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 197 publications
(261 citation statements)
references
References 51 publications
9
247
2
3
Order By: Relevance
“…We recently showed that the Mtb ΔmmpS4/S5 mutant displays a lowiron [c(Fe 3+ ) = 0.5 μM] growth defect and produces less siderophores but is fully capable of siderophore uptake and sensing an iron-deficient state (14). Interestingly, the ΔmmpS4/S5 Significance Many bacteria acquire iron from the environment by secreting small iron-binding molecules called siderophores.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We recently showed that the Mtb ΔmmpS4/S5 mutant displays a lowiron [c(Fe 3+ ) = 0.5 μM] growth defect and produces less siderophores but is fully capable of siderophore uptake and sensing an iron-deficient state (14). Interestingly, the ΔmmpS4/S5 Significance Many bacteria acquire iron from the environment by secreting small iron-binding molecules called siderophores.…”
Section: Resultsmentioning
confidence: 99%
“…S3B). We next sought to determine whether the iron from cMBT was metabolized by the ΔmmpS4/S5 mutant and therefore added cMBT to midlogarithmically growing cells harboring an iron-dependent regulator (IdeR)-dependent GFP reporter (14,20). The cytoplasmic iron reporter indicates iron starvation by fluorescence.…”
Section: Carboxymycobactin and Mycobactin Inhibit The Growth Of Mtbmentioning
confidence: 99%
See 2 more Smart Citations
“…101 MmpL3, MmpL4 e MmpL5 colaboram com o transporte de ferro. 102 MmpL8 tem um papel importante na biogênese de sulfatídeos e também contribui para a virulência do MTB. 103 A proteína MmpL3 tem um papel crucial durante o crescimento do MTB e está envolvida no transporte de ferro, ácidos micólicos e monomicolato trealose.…”
Section: Mmpl3unclassified